Advances in research on malignant transformation of endometriosis-associated ovarian cancer - Chen, Fang; Zhu, Mengying; Li, Wenjuan (Frontiers in Oncology, 2024)
Endometriosis (EMs) is a prevalent chronic gynecological condition that depends on estrogen, marked by the presence of active endometrial tissue (glands and stroma) outside the uterus. Although pathologically benign, it exhibits biological behaviors such as invasion and metastasis akin to malignant tumors. Endometriosis-associated ovarian carcinoma (EAOC), arising from malignant transformation of EMs, poses significant clinical challenges. However, the mechanisms underlying EAOC pathogenesis remain incompletely understood, with a lack of reliable biomarkers for early diagnosis and personalized treatment strategies. Considering the significant number of EMs patients and the extended period during which malignant transformation can occur, EAOC deserves significant attention. Current research both domestically and internationally indicates that the pathogenesis of EAOC is complex, involving genetic mutations, immune microenvironment, oxidative stress, epigenetic changes, and related areas. This review summarizes the mechanisms underlying the development of EAOC.